Marketing Communication Strategy Of Bengkulu Provincial Government Towards Tabut Festival As An International Event - Vethy Octaviani; Martha Heriniazwi Dianthi; Rio Dinero (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
The tourism sector is currently starting to grow again after experiencing a crisis that occurred due to the Covid-19 Pandemic that occurred almost all over the world. This development is utilized by the Bengkulu Provincial Government to develop tourism owned by Bengkulu by holding the 2023 Ark Festival. Unlike the Tabut Festival in previous years, the Bengkulu Provincial Government currently has a strategy to move towards the Tabut Festival as an international event. This research uses descriptive qualitative research methods with data collection through in-depth interviews and literature studies. Therefore, it can be explained that based on segmentation, the Bengkulu Provincial Tourism Office targets local visitors in areas near Bengkulu Province, namely West Sumatra, South Sumatra, Jambi and Lampung. As for international visitors, the target is ASEAN members, Middle Eastern countries and Europe. The visitor target for the 2023 Tabut Festival is 150,000 both internationally and nationally. For now, social media is the priority media in promoting the Festival Tabut. The theme used is’ Keramaian Asli Bengkulu’. This theme is expected to be an attraction for visitors and be able to attract economic movements in Bengkulu Province. However, the obstacle felt by the Tourism Office is the limited media used and the human resources it has. Therefore, to go to the International Event still needs more careful preparation for next year, especially on promotional media and human resources at the Bengkulu City Tourism Office.